2020
DOI: 10.1063/5.0015965
|View full text |Cite
|
Sign up to set email alerts
|

Rashba band splitting in two-dimensional Ruddlesden–Popper halide perovskites

Abstract: Due to the presence of heavy elements and the dynamic nature of hybrid halide perovskites, the strong spin–orbit coupling effect can give rise to Rashba band splitting in these materials. Despite many reports on the Rashba effect in 3D perovskites like CH3NH3PbI3, little is known about its presence in two-dimensional Ruddlesden–Popper (2DRP) perovskites. In this work, we use first-principle calculations to investigate the magnitude and origin of the Rashba effect in three families of 2DRP perovskites. We demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…Through the results it is also indicated that the impacts of tert -BA on the Rashba splitting are more insensitive toward the thickness changing since the surface distortion degree induced by tert -BA does not change obviously with the thickness increasing (Δ θ Br = 14.0°–17.8°), and the splitting energy E R is approximately 50 meV except the 3L model. The overall trend is similar to that previously reported in 2D MAPbI 3 , 17,36 yet without obvious oscillations. The α R values are shown in Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Through the results it is also indicated that the impacts of tert -BA on the Rashba splitting are more insensitive toward the thickness changing since the surface distortion degree induced by tert -BA does not change obviously with the thickness increasing (Δ θ Br = 14.0°–17.8°), and the splitting energy E R is approximately 50 meV except the 3L model. The overall trend is similar to that previously reported in 2D MAPbI 3 , 17,36 yet without obvious oscillations. The α R values are shown in Fig.…”
Section: Resultssupporting
confidence: 90%
“…A theoretical study has discussed the Rashba effect in 2D MAPbI 3 , which has proposed that the distortion degree of the [PbI 6 ] − octahedron is responsible for the magnitude of the Rashba splitting. 36 Consequently, these inconsistent reports indicate that the research about the Rashba effect in 2D HOIPs is still insufficient at present.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the perturbative Hamiltonian of the Rashba effect can be expressed as H R = α R ( k x σ y – k y σ x ), and then the energy dispersion relation should be corrected as . In nearly free electron approximation, the Rashba parameter α R = 2 E 0 / k 0 is used to measure the magnitude of the Rashba effect, in which E 0 is the Rashba energy and k 0 is the k -space shift. As shown in Figure f, the calculated Rashba parameters of 2D α-FAPbI 3 (one to four layers) are 1.42, 1.58, 1.29, and 1.22 eV·Å, respectively, and we can see that the splitting first increases (one to two layers) and then decreases (two to four layers) with thickness.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The capability of the PBEsol functional to provide an accurate description of band gap evolution has also been demonstrated in previous works on chalcogenides, 28 oxides, 13 and halides. 2 More accurate band gap values could be obtained by using a hybrid functional 17,29 and including the effect of spin−orbit coupling, 16,17,29,30 van der Waals forces, 31 and the Rashba effect, 31,32 while they will not affect band gap evolution according to previous works. 16,17,29−31 The excellent agreement of band gap evolution for several representative compounds between PBEsol and Heyd−Scuseria−Ernzerhof (HSE06) screened hybrid functionals 33 (see Figure S1) further confirms that the PBEsol functional can provide a quantitative comparison of band gap evolution.…”
mentioning
confidence: 99%